A Comprehensive Review on Usage Fields of Social Networking Data - M. Sedef DEMİRCİ; Seref SAGIROGLU (Gazi Üniversitesi Fen Bilimleri Dergisi, 2017)
In this study, usage fields of social networking data are classified as a first time in the world literature and handled in 11 different titles in order to understand existing studies that use social data better and also creating new horizons for further studies. In this context, academic and sectoral studies that use social data are examined and important assessments are made for enlightening the future study fields. Finally, it is evaluated that this study will contribute to new projects which will be conducted by university and industry together and also utilizing from social media more.